Annual Development Plan Madhya Pradesh 1962-63 - Planning Commission (Planning Commission, 1962)
Madhya Pradesh, the biggest State of the Indian Union, covers an area of 1,71,210 square miles. It is situated between latitudes 18°N and 26°N and between longitudes 74°E and 84 1/2°E. The main physical features of the State are Gird region, Malwa plateau, Narmada valley. Satpura range and Chhattisgarh plains and the main river systems are Chambal, Betwa, Sone. Narmada, Tapti, Mahanadi and Indravati. The annual rainfall in the State varies from 30" to 60" in Mahakoshal region, 30" to 40" in Madhya Bharat region, 30" to 35" in Vindhya Pradesh region and 30" to 50" in Bhopal region. For administrative purposes, the State is divided into seven divisions, forty-three districts, one hundred and twenty five sub-divisions and one hundred and ninety tahsils, covering 75,561 villages and 219 towns.
Planning and Development Department Madhya Pradesh